Podcast Kearifan Lokal sebagai Media Penguatan Karakter Mahasiswa - Nur Leli Ramli (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
Education providers are one of the sectors forced to change the pattern of offline to online learning due to the COVID-19 pandemic. Students, as members of the native generation, are certainly already familiar with information technology systems that are widely open. When experiencing difficulties, they will use the available platforms to find solutions without communicating directly with the people around them. As a result, they think practically and unconcerned about their environment. Podcasts are an alternative platform for distance learning because they involve professionalism in sharing content or inviting students to collaborate as resource persons. Other students can interact through written communication during learning, allowing feedback to be felt and an emotional connection to be formed. The content of local wisdom values is inserted at every meeting with the goal of instilling and developing student character behaviors. The study included 30 participants, and descriptive statistical analysis revealed that 85% of students were satisfied with using local wisdom podcasts as a learning medium.